Wilt disease reshapes rhizosphere microbiota in small yellow ginger soils - Sun, Qing; Fei, Sitian; Huang, Sihao; Tan, Runtao; Chen, Haibo; Song, Songquan; Wang, Bin (Frontiers in Microbiology, 2025)
IntroductionContinuous cropping obstacles, particularly the prevalent ginger wilt disease (bacterial wilt), severely constrain the sustainable development of the small yellow ginger (Zingiber officinale Roscoe) industry in Rucheng County, China. However, the primary pathogen responsible for this disease in the local cultivar and the associated microbiome shifts within the rhizosphere remain unidentified. This study aimed to elucidate the distinctive rhizosphere microbial community changes induced by ginger wilt disease, identify the potential key pathogen responsible for this disease in Rucheng, and provide a scientific basis for overcoming continuous cropping obstacles in small yellow ginger cultivation.MethodsSoil samples were collected from an uncultivated plot and from the rhizosphere of healthy and wilted small yellow ginger plants. Microbial community structure and composition were analyzed using 16S rRNA gene high-throughput sequencing. Linear Discriminant Analysis (LDA) effect size (LEfSe) was employed to identify differential biomarkers, and functional prediction was performed using BugBase.ResultsGinger wilt disease significantly altered the rhizosphere soil bacterial community structure and composition: the relative abundance of Proteobacteria increased significantly, primarily due to the enrichment of the genus Ralstonia; conversely, the relative abundance of Acidobacteriota, Firmicutes, and Chloroflexi significantly decreased. Ginger wilt disease also significantly reduced the diversity of the rhizosphere soil bacterial community. LEfSe further confirmed Ralstonia as a diagnostic biomarker for ginger wilt disease. BugBase phenotypic prediction indicated that the microbiota enriched in the diseased ginger rhizosphere exhibited higher capabilities for oxidative stress resistance, pathogenic potential, and mobile element content, attributed to a functional consortium of multiple genera, such as Ralstonia as the dominant contributor alongside major contributors such as Rhodanobacter and Dokdonella.DiscussionOur findings highlight that the enrichment of Ralstonia is strongly associated with ginger wilt in Rucheng County and concomitant with profound changes in the rhizospheric microbiota of wilted ginger, involving alterations in both community structure and functional potential.